Stent strut thickness and acute vessel injury during percutaneous coronary interventions: an optical coherence tomography randomized clinical trial. Issue 5 (19th August 2020) - Vilchez-Tschischke, Jean Paul; Salazar, Carlos; Gil-Romero, Jorge; Mori, Ricardo; Nuñez-Gil, Ivan; Quirós, Alicia; Nombela, Luis; del Trigo, Maria; Jimenez-Quevedo, Pilar; Salinas, Pablo; Escaned, Javier; Macaya, Carlos; et al.
Abstract : Aims: Compare the degree of acute vascular injury caused by a polymer-free, thin-strut drug-eluting stent (DES) to that caused by a bioresorbable polymer, thick-strut DES using optical coherence tomography (OCT). Methods and results: Fifty patients requiring nonurgent PCI were randomized to receive either a thin or a thick-strut DES. OCT was performed before and after stent implantation. OCT-based injury score (IS) after implantation was numerically higher within thick-strut stents 0.32 vs. 0.23, but the difference was NS ( P = 0.61). Edge dissections were present in 36% of the patients without differences between groups. Tissue prolapse (TP) area was larger with thin-strut stents (2.26 vs. 1.83 mm 2, P = 0.04). Stent expansion and symmetry index were similar between the two platforms (85% vs. 94%, P = 0.08; and 0.82 vs. 0.80, P = 0.25). No differences were observed in total malapposition area (1.85 mm 2 in thin-strut stents vs. 1.47 mm 2, P = 0.48). Regarding the influence of plaque-type, IS tended to be higher (non-significant) with thick strut DES in fibrocalcific plaques. Stent malapposition area was smaller in fibrous plaques, especially with thin strut stents ( P = 0.03). Conclusion: There was no difference in the extent of OCT-based vessel injury associated with thin and thick-strut DES platforms. TP was larger with the thin strut DES, potentially reflecting a deeper stent embedment in the vessel wall.